2013
DOI: 10.3390/agronomy3030537
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Environmental Stress during Seed Development on Reproductive and Seed Bank Persistence Traits in Wild Oat (Avena fatua L.)

Abstract: Weeds produce seed under a wide range of conditions, depending on timing of emergence, prevailing crop, soil microsites, and climatic conditions, among other factors. We hypothesized that the maturation environment during weed seed development will influence reproductive allocation and seed persistence traits, such as seed dormancy and vigor, and needs to be considered when formulating weed management strategies. This research evaluated the effects of shade and drought stress on reproductive allocation, seed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The authors showed that the content and ratios of 11S/7S proteins were varied among the seven varieties. Normally field conditions encompass genotypes of stress conditions which are not favorable to growth and development of seeds (Gallagher, Granger, Snyder, Pittmann, & Fuerst, ). The predominant abiotic stress in the field conditions are heat and drought which reduces the carbon fixation by the photosynthetic apparatus (Eldakak, Milad, Nawar, & Rohila, ; Farooq, Wahid, Kobayashi, Fujita, & Basra, ).…”
Section: Resultsmentioning
confidence: 99%
“…The authors showed that the content and ratios of 11S/7S proteins were varied among the seven varieties. Normally field conditions encompass genotypes of stress conditions which are not favorable to growth and development of seeds (Gallagher, Granger, Snyder, Pittmann, & Fuerst, ). The predominant abiotic stress in the field conditions are heat and drought which reduces the carbon fixation by the photosynthetic apparatus (Eldakak, Milad, Nawar, & Rohila, ; Farooq, Wahid, Kobayashi, Fujita, & Basra, ).…”
Section: Resultsmentioning
confidence: 99%
“…Species with a wide range of adaptive abilities show diversity in germination of seeds collected from plants grown in different habitats and subjected to differing environmental conditions [15,16]. The habitats investigated in our study differed with respect to soil/climate conditions and crop species with differing competitive ability which determined light access to weeds.…”
Section: Discussionmentioning
confidence: 98%
“…This dormancy strategy works best for annual weeds whose seeds often show conditional, light-mediated dormancy. Drought and shade were found to reduce reproductive allocation and resulted in seed of Avena fatua with less intense primary dormancy than the plants grown under resource-rich conditions, but had no apparent effect on seed vigor [80].…”
Section: Factors Enhance Seed Germination and Dormancy Breakingmentioning
confidence: 89%